2020
DOI: 10.3847/1538-4357/ab7b73
|View full text |Cite
|
Sign up to set email alerts
|

Joint Radial Velocity and Direct Imaging Planet Yield Calculations. I. Self-consistent Planet Populations

Abstract: Planet yield calculations may be used to inform the target selection strategy and science operations of space observatories. Forthcoming and proposed NASA missions, such as the Wide-Field Infrared Survey Telescope (WFIRST), the Habitable Exoplanet Imaging Mission (HabEx), and the Large UV/Optical/IR Surveyor (LUVOIR), are expected to be equipped with sensitive coronagraphs and/or starshades. We are developing a suite of numerical simulations to quantify the extent to which ground-based radial velocity (RV) sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 68 publications
3
28
0
Order By: Relevance
“…(2019) at separations beyond 10 au. Dulz et al (2020) fit model distributions of planets to occurrence rates measured from Kepler and previous RV surveys. Although their constraints on Jovian-mass planets were relatively weak, they found that the occurrence of Neptune-mass and smaller planets must fall off beyond ∼5 au due to dynamical constraints.…”
Section: Comparison To Previous Rv Surveysmentioning
confidence: 99%
“…(2019) at separations beyond 10 au. Dulz et al (2020) fit model distributions of planets to occurrence rates measured from Kepler and previous RV surveys. Although their constraints on Jovian-mass planets were relatively weak, they found that the occurrence of Neptune-mass and smaller planets must fall off beyond ∼5 au due to dynamical constraints.…”
Section: Comparison To Previous Rv Surveysmentioning
confidence: 99%
“…The exoplanet occurrence rates were based on the EXOPAG SAG-13 power law model of Kepler data, as modified by Dulz et al 38 for large mass and large semimajor axis planets.…”
Section: Astrophysical Inputsmentioning
confidence: 99%
“…However, a further option to explore the possible planetary architecture of Beta CVn, particularly given the proximity of the star, is direct imaging (Kane et al 2018;Dulz et al 2020).…”
Section: Potential For Terrestrial Planetsmentioning
confidence: 99%